Synthesis method of solid electrolyte material

Nano-titanium aluminum lithium phosphate (LATP) was prepared through four-step sintering method, which solved the problems of flammable and explosive electrolytes and lithium dendrites in lithium-ion batteries, and achieved the safety and performance improvement of lithium-ion batteries, and the process is controllable and equipment is available. Small investment.

CN119118089AActive Publication Date: 2024-12-13HEFEI GUOXUAN HIGH TECH POWER ENERGY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411261059.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The organic liquid or gel electrolyte used in existing lithium-ion batteries is flammable and explosive, and the lithium metal negative electrode is prone to lithium dendrites to cause internal short circuit, which limits the increase in battery energy density, and nanophosphoric acid synthesized by conventional solid-phase method The particle size of titanium aluminum lithium (LATP) is difficult to reach below 100nm, which affects the safety and performance of the battery.

Method used

NanoLATP is prepared by four-step sintering method, including low-temperature oxidation, protective atmosphere high-temperature sintering, low-temperature oxidation and carbon removal and dynamic high-temperature sintering. Through these steps, LATP particles are controlled to be ≤10nm, improve their dispersion and crystallinity, and form high ion conduction. nanoscale materials of rate.

Benefits of technology

It has achieved improved safety, increased energy density, extended cycle life of lithium-ion batteries, and controlled process, small equipment investment, and good product batch stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118089A_ABST
    Figure CN119118089A_ABST
Patent Text Reader

Abstract

The invention discloses a synthesis method of a solid electrolyte material. The method comprises the following steps: oxidizing an LATP precursor at low temperature; sintering the precursor at high temperature for a short time in a protective atmosphere; performing low-temperature oxidation removal; and dynamically sintering at high temperature to remove carbon. The solid electrolyte nano lithium titanium aluminum phosphate LATP material prepared by the method has high ionic conductivity, and the lithium ion battery prepared from the material has low low-temperature DCR (Direct Current Ratio), high capacity exertion and excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolyte materials for lithium ion batteries, in particular to a method for synthesizing solid electrolyte materials, and more particularly to a method for synthesizing nano solid electrolyte lithium titanium aluminum phosphate materials. Background Art

[0002] Lithium-ion batteries have been widely used in electric vehicles, power tools, and energy storage due to their high energy density, light weight, high voltage, safety, and low environmental pollution. At present, commercial lithium-ion batteries mostly use organic liquid electrolytes or gel electrolytes, which are flammable and explosive, resulting in great safety hazards. In addition, lithium metal negative electrodes are prone to lithium dendrites, which can pierce the diaphragm and cause internal short circuits, triggering thermal runaway. Therefore, conventional lithium-ion batteries cannot use lithium metal as the negative electrode, which limits the further improvement of battery energy density.

[0003] Solid electrolytes can improve the safety of lithium-ion batteries due to their high thermal stability and effective inhibition of lithium negative electrode dendrite growth. Solid electrolytes are mainly divided into three systems: polymer electrolytes, oxide electrolytes and sulfide electrolytes. Among them, oxide electrolytes have attracted much attention and research from scientific researchers due to their high energy density, excellent stability, long cycle life and low cost. Lithium aluminum titanium phosphate, or LATP, as a typical oxide solid electrolyte, has also become one of the research focuses. Particle size plays a vital role in ionic conductivity. In addition, particle size also affects the density of the solid electrolyte membrane, affects the overall lithium ion conductivity of the solid-state battery, and is not conducive to the performance of the capacity and rate performance of the solid-state battery. Therefore, the synthesis of nanoscale LATP is extremely critical. The main methods for LATP synthesis include solid phase method, sol-gel method, etc. LATP synthesized by solid phase method generally has large particles and is very easy to agglomerate. In the later stage, the particle size cannot be less than 100nm through air flow crushing and / ball milling, and the true nanoscale cannot be achieved. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention aims to provide a synthesis method and application of a solid electrolyte material.

[0005] The method for synthesizing the solid electrolyte material provided by the present invention comprises the following steps:

[0006] 1) The LATP precursor is crushed, then placed in an oxidizing atmosphere, heated to reaction temperature 1, kept warm, and then cooled to room temperature;

[0007] 2) heating the material obtained in 1) to reaction temperature 2 in an inert atmosphere, keeping the temperature, and then cooling to room temperature;

[0008] 3) crushing the material obtained in 2), and then placing it in an oxidizing atmosphere, heating it to a reaction temperature of 3, keeping it warm, and then cooling it to room temperature;

[0009] 4) The material obtained in step 3) is placed in a dual-temperature zone reactor, first evacuated, then oxygen is introduced from the bottom, then evacuated, then ventilated from the top, and then vibrated. The above process is repeated for a period of time, and then cooled to room temperature to obtain nano-LATP material.

[0010] The present invention prepares nano-LATP by a four-step sintering method. The first step is to oxidize the LATP precursor at low temperature to carbonize the organic matter in the precursor, and at the same time remove most of the free water and bound water in the organic matter, and enrich lithium, aluminum, titanium and phosphorus elements; the second step is to sinter the precursor at high temperature for a short time in a protective atmosphere, so that lithium, aluminum, titanium and phosphorus elements react to generate amorphous LATP, the high-temperature sintering time is short, and there is a protective atmosphere, so the surface of the generated amorphous LATP is wrapped by a large amount of carbon, which can effectively inhibit the growth of LATP and maintain a primary particle size of ≤10nm; the third step is low-temperature oxidation and carbon removal, by adopting step temperature insulation oxidation, it can effectively avoid the heat released by carbon decomposition causing the local temperature to be too high, resulting in further growth of LATP particles, and the carbon on the surface of LATP will not be completely removed during the low-temperature oxidation and carbon removal process, and a small amount of carbon will still be retained; the fourth step is dynamic high-temperature sintering and carbon removal, and the LATP is treated by dynamic high-temperature sintering. On the one hand, it can avoid the agglomeration of nano-LATP particles causing excessive particle growth, and on the other hand, it can fully remove carbon and further improve the crystallinity of LATP.

[0011] In step 1) of the above method, the chemical formula of the LATP precursor is: Li 1+x Al x Ti 2-x (PO4)3, where x is 0.3 to 0.5;

[0012] Specifically, the LATP precursor is prepared by a method comprising the following steps:

[0013] Obtain a lithium source, an aluminum source, a titanium source, a phosphorus source, an acidic chelating agent and an alcohol solvent; prepare the acidic chelating agent into an acidic chelating agent aqueous solution, add the titanium source to the acidic chelating agent aqueous solution, and stir for 2 to 6 hours to obtain a first mixed solution; then add the lithium source and the phosphorus source to the first mixed solution, and stir for 1 to 5 hours to obtain a second mixed solution; then add the aluminum source to the second mixed solution, and stir for 1 to 5 hours to obtain a third mixed solution; add the alcohol solvent to the third mixed solution to obtain a liquid sol; adjust the pH of the liquid sol to 6 to 8 to obtain a neutral liquid sol, and dry the neutral liquid sol to obtain a LATP precursor.

[0014] Wherein, the lithium source is one or more of lithium carbonate, lithium nitrate, lithium hydroxide and lithium oxide;

[0015] The aluminum source is one or more of aluminum carbonate, aluminum nitrate, aluminum oxide, aluminum hydroxide and aluminum chloride;

[0016] The titanium source is one or more of titanic acid, tetraethyl titanate, tetrabutyl titanate and isopropyl titanate;

[0017] The phosphorus source is one or more of phosphoric acid, diammonium phosphate, diammonium hydrogen phosphate and ammonium phosphate;

[0018] The acidic complexing agent is one or more of citric acid, malic acid, malonic acid, succinic acid, succinic acid, glycolic acid, aminoacetic acid, lactic acid, tartaric acid and ethylenediaminetetraacetic acid;

[0019] The alcohol solvent is one or more of anhydrous ethanol, ethylene glycol and glycerol;

[0020] The molar ratio of lithium source, aluminum source, titanium source and phosphorus source conforms to the following chemical formula: Li 1+x Al x Ti 2-x (PO4)3, where x is 0.3 to 0.5;

[0021] The mass concentration of the acidic complexing agent aqueous solution is 40-60wt.%;

[0022] The molar ratio of the sum of the moles of the acidic complexing agent and the alcohol solvent to the metal cation in the liquid sol is (6-10):1;

[0023] The molar ratio of the acidic complexing agent to the alcohol solvent is 1:1;

[0024] The drying temperature of the neutral liquid sol is 100-150° C., and the drying time is 10-15 hours.

[0025] In step 1), the particle size of the LATP precursor after crushing is controlled to be Dmin≥0.8μm, D10≥1.2μm, D50 is 2.0-10μm, D90≤15μm, and Dmax≤20μm;

[0026] The oxidizing atmosphere is a mixed gas of air and oxygen, wherein the oxygen concentration is controlled at 21-95%;

[0027] The reaction temperature 1 is 300-500°C, and the holding time is 5-20h;

[0028] In step 2), the inert atmosphere is a mixture of one or more gases selected from nitrogen, helium, neon, argon, krypton, xenon and radon;

[0029] Reaction temperature 2 is 600-800°C, and the holding time is 0.5-2.0h;

[0030] In step 3), the particle size of the material after crushing is controlled to be Dmin≥30nm, D10≥50nm, D50 is 100-300nm, D90≤500nm, and Dmax≤1.0μm;

[0031] The oxidizing atmosphere is a mixed gas of air and oxygen, wherein the oxygen concentration is controlled at 21-95%;

[0032] Reaction temperature 3 is a step temperature, the temperature range is controlled at 300-500°C, and the insulation time of each step temperature is 3-10 hours; specifically, it can be heated to 400°C, 450°C, and 475°C in sequence, and each temperature is kept for 5 hours;

[0033] In step 4), the temperature of the upper temperature zone of the dual-temperature zone reactor is controlled at 650-750° C., and the temperature of the lower temperature zone is controlled at 750-850° C.;

[0034] The pressure in the reaction furnace is maintained at -0.04 to -0.08 MPa by exhausting air, and then oxygen is blown in from the bottom for 1 to 10 seconds, the oxygen pressure is 0.2 to 0.8 MPa, and then it is left to stand for 2 to 10 minutes, and then the pressure in the furnace is maintained at -0.04 to -0.08 MPa, and then oxygen is blown in from the top for 1 to 10 seconds, and it is left to stand for 0.5 to 5 minutes, and the furnace body is vibrated once by an air hammer, and this is repeated 100 to 500 times. The obtained nano-LATP material is a secondary particle agglomerated from the primary particles, wherein the primary particle size is ≤10nm, and the secondary particle size is ≤40nm; it is well dispersed, and the ion conductivity is ≥7×10 -4 S / cm.

[0035] The nano lithium aluminum titanium phosphate LATP material prepared by the above method and its application in lithium ion batteries also fall within the protection scope of the present invention.

[0036] The present invention also provides a lithium ion battery, wherein the lithium ion battery uses the nano lithium aluminum titanium phosphate LATP material as a solid electrolyte.

[0037] The beneficial effects of the present invention are:

[0038] 1. The present invention adopts a four-step sintering method to prepare nano-LATP. First, the LATP precursor is oxidized at low temperature. The organic matter in the precursor is carbonized, most of the free water and bound water in the organic matter are removed, and lithium, aluminum, titanium and phosphorus are enriched. The second step is to sinter the precursor at high temperature for a short time in a protective atmosphere, so that lithium, aluminum, titanium and phosphorus react to generate amorphous LATP. Since the high-temperature sintering time is short and there is a protective atmosphere, the surface of the generated amorphous LATP is wrapped with a large amount of carbon, which can effectively inhibit the growth of LATP and maintain a primary particle size of ≤10nm. The third step is low-temperature oxidation and carbon removal. This step adopts step temperature insulation oxidation, which can effectively avoid the local temperature being too high due to the release of heat from carbon decomposition, resulting in further growth of LATP particles. In order to make nano-LATP have good dispersibility and reduce agglomeration, the carbon on the surface of LATP will not be completely removed during the low-temperature oxidation and carbon removal process in the third step, and a small amount of carbon will still be retained. The fourth step is dynamic high-temperature sintering and carbon removal. The dynamic high-temperature sintering method is used to treat LATP. On the one hand, it can avoid the excessive growth of particles caused by the agglomeration of multiple nano-LATP particles. On the other hand, it can fully remove carbon and further improve the crystallinity of LATP.

[0039] 2. The nano LATP synthesized in the present invention has a primary particle size of ≤10nm, a secondary particle size of ≤40nm, good dispersion, and an ion conductivity of ≥7×10 -4 S / cm.

[0040] 3. The invention has small equipment investment, controllable process and good batch stability of products. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The XRD diagrams of the intermediates and finished products in the process of preparing the nano-LATP material in Example 1 of the present invention are shown.

[0042] Figure 2 This is a TEM image of the nano-LATP material prepared in Example 1 of the present invention.

[0043] Figure 3 This is a TEM image of LATP prepared in Comparative Example 1 of the present invention.

[0044] Figure 4 Comparison of XRD spectra of LATP materials prepared in Example 1 of the present invention and Comparative Example 1.

[0045] Figure 5 The LATP-coated LiNi prepared in Example 5 of the present invention 0.88 Co 0.07 Mn 0.05 SEM image of O2 single crystal ternary material.

[0046] Figure 6 The LATP-coated LiNi prepared in Example 5 of the present invention0.88 Co 0.07 Mn 0.05 TEM image of O2 single crystal ternary material.

[0047] Figure 7 The LATP-coated LiNi prepared in Comparative Example 8 of the present invention 0.88 Co 0.07 Mn 0.05 SEM image of O2 single crystal ternary material.

[0048] Figure 8 The LATP-coated LiNi prepared in Comparative Example 8 of the present invention 0.88 Co 0.07 Mn 0.05 TEM image of O2 single crystal ternary material.

[0049] Fig. 9 The LATP-coated LiNi prepared in Comparative Example 9 of the present invention 0.88 Co 0.07 Mn 0.05 TEM image of O2 single crystal ternary material. DETAILED DESCRIPTION

[0050] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0051] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0052] The first aspect of the present invention discloses a method for synthesizing a nano-lithium aluminum titanium phosphate material, which specifically comprises the following steps:

[0053] S1, breaking the LATP precursor, then placing it in an oxidizing atmosphere, heating it to reaction temperature 1, keeping it warm, and then cooling it to room temperature;

[0054] S2, heating the material obtained in step S1 to reaction temperature 2 in an inert atmosphere, keeping the temperature and then cooling to room temperature;

[0055] S3, crushing the material obtained in S2, and then placing it in an oxidizing atmosphere, heating it to a reaction temperature of 3, keeping it warm, and then cooling it to room temperature;

[0056] S4, taking the material obtained in step S3 and placing it in a dual-temperature zone reactor, first evacuating the air, then introducing oxygen from the bottom, evacuating the air again, then ventilating the top, and then vibrating. The above process is repeated for a period of time, and the nano-LATP material is obtained after cooling to room temperature.

[0057] The present invention adopts a four-step sintering method to prepare nano-LATP. First, the LATP precursor is oxidized at low temperature. The organic matter in the precursor is carbonized, most of the free water and bound water in the organic matter are removed, and lithium, aluminum, titanium and phosphorus elements are enriched. The second step is to sinter the precursor at high temperature for a short time in a protective atmosphere, so that lithium, aluminum, titanium and phosphorus elements react to generate amorphous LATP. Since the high-temperature sintering time is short and there is a protective atmosphere, the surface of the generated amorphous LATP is wrapped by a large amount of carbon, which can effectively inhibit the growth of LATP and maintain a primary particle size of ≤10nm. The third step is low-temperature oxidation and carbon removal. This step adopts step temperature insulation oxidation, which can effectively avoid the local temperature being too high due to the release of heat by carbon decomposition, resulting in further growth of LATP particles. In order to make the nano-LATP have good dispersibility and reduce agglomeration, the carbon on the surface of LATP will not be completely removed during the low-temperature oxidation and carbon removal process in the third step, and a small amount of carbon will still be retained. The fourth step is dynamic high-temperature sintering and carbon removal. The LATP is treated by dynamic high-temperature sintering, which can avoid the excessive growth of particles caused by the agglomeration of multiple nano-LATP particles, and can also fully remove carbon and further improve the crystallinity of LATP. The nano-LATP synthesized by the present invention has a primary particle size of ≤10nm, a secondary particle size of ≤40nm, good dispersion, and an ion conductivity of ≥7×10 -4 S / cm.

[0058] Furthermore, the chemical formula of the LATP precursor in step S1 is: Li 1+x Al x Ti 2-x (PO4)3, where x is 0.3-0.5, is prepared according to the method described in patent CN202211268119.8.

[0059] Furthermore, in the step S1, the particle size of the LATP precursor after crushing is controlled to be Dmin≥0.8μm, D10≥1.2μm, D50 is 2.0-10μm, D90≤15μm, and Dmax≤20μm;

[0060] Furthermore, in the steps S1 and S3, the oxidizing atmosphere is a mixed gas of air and oxygen, wherein the oxygen concentration is controlled at 21-95%;

[0061] Furthermore, in step S1, the reaction temperature 1 is 300-500° C., and the insulation time is 5-20 h;

[0062] Furthermore, the inert atmosphere in step S2 is a mixture of one or more gases selected from nitrogen, helium, neon, argon, krypton, xenon and radon;

[0063] Furthermore, in step S2, the reaction temperature 2 is 600-800° C., and the holding time is 0.5-2.0 h;

[0064] Furthermore, in step S3, the particle size of the material after crushing is controlled to be Dmin≥30nm, D10≥50nm, D50 is 100-300nm, D90≤500nm, and Dmax≤1.0μm;

[0065] Furthermore, in step S3, the reaction temperature 3 is a step temperature, the temperature range is controlled to be 300-500° C., and the insulation time of each step temperature is 3-10 hours;

[0066] Furthermore, in step S4, the reaction furnace is divided into two temperature zones, the temperature of the upper temperature zone is controlled at 650-750° C., and the temperature of the lower temperature zone is controlled at 750-850° C.;

[0067] Furthermore, in step S4, air is pumped out to maintain the air pressure in the reaction furnace chamber at -0.04 to -0.08 MPa, and then oxygen is blown into the reaction furnace chamber from the bottom for 1 to 10 seconds, the oxygen pressure is 0.2 to 0.8 MPa, and then the reaction furnace chamber is allowed to stand for 2 to 10 minutes, and then air is pumped out again to maintain the air pressure in the reaction furnace chamber at -0.04 to -0.08 MPa, and then oxygen is blown into the reaction furnace chamber from the top for 1 to 10 seconds, and the reaction furnace chamber is allowed to stand for 0.5 to 5 minutes. The furnace body is vibrated once with an air hammer, and the process is repeated 100 to 500 times.

[0068] Another aspect of the present invention provides an application of the nano-lithium aluminum titanium phosphate LATP material in a lithium ion battery, wherein the nano-lithium aluminum titanium phosphate LATP material is used as a solid electrolyte of a lithium ion battery. The nano-lithium aluminum titanium phosphate LATP material has high ion conductivity, and a lithium ion battery prepared therefrom has low low-temperature DCR, high capacity utilization, and excellent cycle performance.

[0069] Example 1

[0070] The LATP precursor was prepared according to the method described in Example 1 of patent CN202211268119.8. The specific operation was as follows: lithium carbonate, aluminum carbonate, tetraethyl titanate, and phosphoric acid were prepared according to the mass ratio of elements Li:Al:Ti:P=1.3:0.3:1.7:3. At the same time, citric acid and anhydrous ethanol were prepared according to the mass ratio (citric acid + anhydrous ethanol): (Li + +Al 3+ +Ti 4+)=7:1, wherein the mass ratio of citric acid to anhydrous ethanol is 1:1. After the preparation is completed, citric acid is first configured into a citric acid solution with a concentration of 40%wt. Subsequently, tetraethyl titanate, lithium carbonate and phosphoric acid, aluminum carbonate and anhydrous ethanol are added in four steps in sequence, and the addition process is accompanied by stirring. After the addition, stirring is continued for 3h, 2h, 2h and 1h respectively, and then a liquid sol is obtained. Ammonia water is added to the liquid sol, and the pH value is adjusted to 7.0. The liquid sol is then placed in an oven at 110°C and dried for 2h to finally obtain a LATP precursor.

[0071] The LATP precursor was air flow crushed to control the particle size D50 to 5.0 μm (Dmin = 0.85 μm, D10 = 1.52 μm, D50 = 5.0 μm, D90 = 10.54 μm, Dmax = 17.59 μm), and then placed in dry compressed air (oxygen concentration of 25%), heated to 400 ° C at a heating rate of 2 ° C / min, and kept warm for 8 hours. After the heat preservation, it was naturally cooled to room temperature to obtain a pretreated LATP precursor;

[0072] The pretreated LATP precursor was heated to 700°C at a rate of 10°C / min in a nitrogen atmosphere, kept at this temperature for 1.0 h, and then cooled to room temperature by nitrogen air cooling to obtain carbon-coated amorphous LATP;

[0073] The carbon-coated amorphous LATP was crushed by air flow crushing equipment, and the D50 particle size was controlled to be 188nm (Dmin=41nm, D10=65nm, D50=188nm, D90=471nm, Dmax=723nm). It was then placed in dry compressed air (oxygen concentration was 25%) and heated to 400°C, 450°C, and 475°C in sequence at a heating rate of 2°C / min. Each temperature was kept for 5h, and then naturally cooled to room temperature.

[0074] Finally, the LATP is placed in a dual-temperature zone reactor, with the upper temperature zone of the reactor at 700°C and the lower temperature zone at 800°C. First, evacuate the air to reduce the pressure in the reactor chamber to -0.06MPa, then introduce oxygen from the bottom for 4s, with an oxygen pressure of 0.4MPa, and let it stand for 5min. Then evacuate the air again to reduce the pressure in the reactor chamber to -0.06MPa again, introduce oxygen from the top for 4s, let it stand for 2min, and vibrate the furnace body once with an air hammer. Repeat the above steps 200 times. Then naturally cool it down to room temperature to obtain highly dispersed nano LATP powder.

[0075] The pretreated LATP precursor was subjected to high-temperature sintering in protective atmosphere, low-temperature gradient oxidation and dynamic high-temperature sintering to obtain intermediates and finished products for XRD characterization, such as Figure 1It can be found that the pretreated LATP precursor is amorphous LATP after sintering in a protective atmosphere, and then after low-temperature gradient oxidation, the crystallinity of LATP is improved. Finally, after dynamic high-temperature sintering, LATP has good crystallinity.

[0076] Figure 2 This is the TEM image of the prepared nano-LATP material.

[0077] Comparative Example 1

[0078] Lithium carbonate, aluminum carbonate, tetraethyl titanate, and phosphoric acid were mixed in a mass ratio of Li:Al:Ti:P=1.3:0.3:1.7:3, and then placed in dry compressed air (oxygen concentration of 25%) at a heating rate of 2°C / min to 700°C, kept warm for 10 hours, and naturally cooled to room temperature. Subsequently, a jet mill was used for crushing, and the particle size D50 was controlled to be 200nm. The LATP powder prepared by the solid phase method was obtained.

[0079] Figure 3 This is the TEM image of the prepared LATP.

[0080] Compare Figure 2 and Figure 3 It was found that the LATP in Example 1 was secondary particles agglomerated from primary particles, with a primary particle size of 6 nm and a secondary particle size of 25 nm. The LATP particles synthesized in Comparative Example 1 had different sizes, and the particle size was generally larger. The average particle size was measured to be 180 nm.

[0081] Figure 4 The XRD spectra of the LATP materials prepared in Example and Comparative Example 1 are shown in FIG. Figure 4 It can be seen that the substances synthesized by both are LATP phases.

[0082] Example 2

[0083] After the LATP precursor is crushed by air flow, low-temperature oxidation is performed, and the sintering temperature is increased to 500° C. The other steps are the same as those in Example 1.

[0084] Comparative Example 2

[0085] After the LATP precursor is crushed by air flow, low-temperature oxidation is performed, and the sintering temperature is increased to 600° C. The other steps are the same as those in Example 1.

[0086] Example 3

[0087] The high-temperature sintering holding time of the pretreated LATP precursor at 700° C. in a nitrogen atmosphere was extended to 2.0 h, and the other steps were the same as those in Example 1.

[0088] Comparative Example 3

[0089] The pretreated LATP precursor was sintered at 700° C. for 1 h in dry compressed air (oxygen concentration was 25%). The other steps were the same as those in Example 1.

[0090] Comparative Example 4

[0091] The high-temperature sintering holding time of the pretreated LATP precursor at 700° C. in a nitrogen atmosphere was extended to 5 h, and the other steps were the same as those in Example 1.

[0092] Example 4

[0093] The carbon-coated amorphous LATP was placed in dry compressed air and heated to 400°C, 450°C, and 475°C at a heating rate of 2°C / min, each temperature was kept for 9 hours, and then naturally cooled to room temperature. The other steps were the same as in Example 1.

[0094] Comparative Example 5

[0095] The carbon-coated amorphous LATP was placed in dry compressed air and heated to 400°C, 450°C, and 475°C at a heating rate of 2°C / min, each temperature was kept for 20 hours, and then naturally cooled to room temperature. The other steps were the same as in Example 1.

[0096] Comparative Example 6

[0097] After the carbon-coated amorphous LATP was subjected to gradient temperature low-temperature oxidation, it was placed in an oxygen atmosphere and heated to 700° C. at a heating rate of 2° C. / min and kept at that temperature for 5 h. The other steps were the same as those in Example 1.

[0098] Comparative Example 7

[0099] LATP was prepared using the method of Example 3 in patent CN202211268119.8.

[0100] test

[0101] 1. The LATP samples prepared in Examples 1-4 and Comparative Examples 1-6 were characterized by TEM. With the help of NanoMeasurer1.2 software, the above TEM images were imported into the software, the scale was set, and then the length of each particle was measured in the longest direction. Finally, the lengths of all the measured particles were averaged. The secondary particles were large particles composed of multiple primary particles. The TEM images showed that there were a large number of "black" primary particles inside the secondary particles. The primary average particle size and the secondary average particle size were obtained by measuring the lengths of the primary particles and the secondary particles and averaging them.

[0102] 2. The LATP materials prepared in Examples 1-4 and Comparative Examples 1-6 were placed in a mold, maintained at a pressure of 18 MPa for 5 minutes, pressed into a disc with a diameter of 10 mm and a thickness of 3 mm, and then placed in a muffle furnace, heated to 950°C at a rate of 5°C / min, and kept warm for 5 hours. After the insulation was completed, the disc was naturally cooled to room temperature, and after sintering, it was polished with sandpaper until smooth, and the surface residue was removed to obtain the corresponding solid electrolyte sheet. The solid electrolyte sheets of Examples 1-4 and Comparative Examples 1-6 obtained above were respectively subjected to gold spraying treatment, with a gold spraying thickness of ~30 nm, and then sandpaper polishing treatment was used after gold spraying, and then placed in a battery mold and pressed to obtain a test sample, and the ionic conductivity of the above samples at 25°C was tested by the AC impedance method. The specific test results are shown in Table 1.

[0103] Table 1 shows the primary average particle size, secondary average particle size and ionic conductivity data of the LATP materials obtained in the above examples and comparative examples:

[0104] Table 1

[0105]

[0106] It can be seen from Table 1 that although the materials obtained in Example 1 and Comparative Example 2 are both LATP phases, the ionic conductivity of the two is quite different, with the former being 4.89×10 -4 S / cm.

[0107] Compared with Example 1-2, the low-temperature oxidation temperature of Comparative Example 2 is increased, resulting in the growth of primary particles and the decrease of ionic conductivity.

[0108] In Comparative Example 3, compared with Example 1, the high-temperature sintering atmosphere is changed and air is introduced, which will lead to more carbon loss and weaken the ability of carbon to inhibit the growth of LATP particles, thereby causing the LATP particles to grow and the ionic conductivity to decrease.

[0109] Compared with Examples 1 and 3, the high-temperature sintering time in the protective atmosphere of Comparative Example 4 was prolonged, resulting in further growth of the particles and reduced ionic conductivity.

[0110] Compared with Examples 1 and 4, Comparative Example 5 prolongs the low-temperature carbon removal time, resulting in further growth of particles and reduced ion conductivity.

[0111] Compared with Example 1, in Comparative Example 6, the dynamic high-temperature sintering is changed to static sintering, which increases the contact between particles, further grows the LATP particles, and reduces the ionic conductivity.

[0112] Compared with Example 1, the sintering system of the LATP precursor in Comparative Example 7 is different, resulting in larger LATP particle size, lower ion conductivity, and reduced surface carbon content.

[0113] Example 5

[0114] The nano-LATP synthesized in Example 1 was used to coat LiNi 0.88 Co 0.07 Mn 0.05 O2 single crystal ternary material, the coating amount of LATP is 0.5% of the mass of the single crystal ternary material. The specific coating process is: take 1000gLiNi 0.88 Co 0.07 Mn 0.05 The O2 single crystal ternary material and 5g of the LATP synthesized in Example 1 were added to a 3L polyethylene barrel, and then 500g of alumina balls with a diameter of 12mm were added according to a material-ball ratio of 2:1. After sealing, the mixture was mixed for 3h using a 3D mixer. The mixed material was placed in an oxygen atmosphere, heated from room temperature to 550°C, and kept warm for 5h. After the insulation was completed, it was naturally cooled to room temperature to obtain nano-LATP-coated LiNi 0.88 Co 0.07 Mn 0.05 O2 single crystal ternary material, and conduct battery charging and full battery performance evaluation.

[0115] Comparative Example 8

[0116] Nano-LATP synthesized in Comparative Example 1 is used to coat LiNi 0.88 Co 0.07 Mn 0.05 For O2 single crystal ternary material, the coating amount of LATP is 0.5% of the mass of the single crystal ternary material, and the battery charging and full battery performance evaluation are carried out.

[0117] Comparative Example 9

[0118] Nano-LATP synthesized in Comparative Example 7 is used to coat LiNi 0.88 Co 0.07 Mn 0.05 For O2 single crystal ternary material, the coating amount of LATP is 0.5% of the mass of the single crystal ternary material, and the battery charging and full battery performance evaluation are carried out.

[0119] Example 6

[0120] 1. LiNi was coated with the nano-LATP in Example 5 and Comparative Example 7. 0.88 Co 0.07 Mn 0.05 The O2 single crystal ternary material, conductive agent SP and binder PVDF are prepared in a mass ratio of 97.5:1:1.5 with NMP as solvent to make the electrode, which is then coated on a carbon-coated aluminum foil, dried at 100°C for 5 hours, and compacted on a roller press to obtain the positive electrode.

[0121] The metal lithium sheet was used as the negative electrode, 1M LiPF6 solution was used as the electrolyte, and cell gard2300 was used as the separator. They were assembled into button cells with the above positive electrode sheets. The charge and discharge were carried out at a rate of 0.2C within the cut-off voltage range of 2.8 to 4.35V. The results are shown in Table 2.

[0122] 2. The nano-LATP in Example 5 and Comparative Example 7 were coated with LiNi 0.88 Co 0.07 Mn 0.05 O2 single crystal ternary material, conductive agent CNTs, and binder PVDF are mixed in a mass ratio of 98:1:1, with NMP as solvent, and the solid content is controlled to 70%. Then it is coated on the current collector aluminum foil, and the single surface density is controlled to 215g / m 2 After rolling, the compaction density of the pole piece is 3.60g / cm 3 According to the NP ratio of 1.13, it was matched with the silicon-carbon negative electrode, 1M LiPF6 solution was used as the electrolyte, Cellgard2300 was used as the separator, and a 3Ah soft pack battery was assembled. The electrochemical performance of the product is shown in Table 2.

[0123] Example 5 and Comparative Example 8 respectively use LATP prepared in Example 1 and Comparative Example 1 to coat LiNi 0.88 Co 0.07 Mn 0.05 O2 single crystal ternary material, the obtained sample is scanned and characterized as follows Figure 5 and Figure 7 , the transmission characterization is performed as Figure 6 and Figure 8 It was found that the LATP synthesized in Example 1 could be evenly coated on the surface of the material, while the LATP synthesized in Comparative Example 1 coated the material unevenly and showed an island-like distribution.

[0124] Since LATP belongs to the lithium-poor phase, it will react with the residual alkali on the surface of the ternary material at high temperature to reduce the residual alkali content of the material. As can be seen from Table 2, the residual alkali content of Comparative Example 8 is higher than that of Example 5, mainly because the latter is uniformly coated and reacts with more residual alkali, while the former is unevenly coated, and the probability of reaction with residual alkali is reduced. In addition, the ternary material capacity of the LATP prepared in Example 1 coated in Example 5 is higher, the cycle performance and low-temperature power performance are better, and the DSC peak decomposition temperature is higher, which are all related to uniform coating and high ionic conductivity. LATP is a fast ion conductor, and its coating on the surface of the ternary material will increase the ionic conductivity of the material, and uniform coating is more conducive to the material capacity and power performance. And uniform coating can reduce the contact area between the ternary material and the electrolyte, reduce the occurrence of side reactions, and can also increase the thermal failure temperature of the ternary material.

[0125] Comparative Example 9: LiNi coated with LATP prepared in Comparative Example 70.88 Co 0.07 Mn 0.05 O2 single crystal ternary material, the obtained sample is characterized by transmission Fig. 9 Compared with Example 5, it was found that the LATP synthesized in Comparative Example 7 was not evenly coated on the material surface, and some areas of the material surface were exposed.

[0126] As shown in Table 2, the residual alkali content in Comparative Example 9 is higher than that in Example 5, mainly because the former cannot be coated uniformly, and the probability of reacting with the residual alkali on the surface of the material is reduced. 0.88 Co 0.07 Mn 0.05 Compared with Example 5, the capacity of the O2 single crystal ternary material is lower, the cycle performance and low temperature power performance are worse, and the DSC peak decomposition temperature is lower, which is related to the uneven coating and low ionic conductivity. The uniformity of LATP coating is related to its surface carbon content. Carbon helps nano-LATP to be more easily dispersed during the coating of the positive electrode material.

[0127] Table 2

[0128]

[0129] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.

Claims

1. A method for synthesizing a solid electrolyte material, characterized in that: The method comprises the following steps: 1) crushing the LATP precursor, placing it in an oxidizing atmosphere, heating it to a reaction temperature of 1, keeping it warm and then cooling it to room temperature; 2) heating the material obtained in 1) to reaction temperature 2 in an inert atmosphere, keeping the temperature and then cooling to room temperature; 3) crushing the material obtained in 2), and then placing it in an oxidizing atmosphere, heating it to a reaction temperature of 3, keeping it warm, and then cooling it to room temperature; 4) The material obtained in step 3) is placed in a dual-temperature zone reactor, first evacuated, then oxygen is introduced from the bottom, then evacuated, then ventilated from the top, and then vibrated. The above process is repeated for a period of time, and then cooled to room temperature to obtain nano-LATP material.

2. The method according to claim 1, characterized in that In step 1), the chemical formula of the LATP precursor is: Li 1+x Al x Ti 2-x (PO4)3, where x is 0.3 to 0.5; The LATP precursor is prepared by a method comprising the following steps: Obtaining a lithium source, an aluminum source, a titanium source, a phosphorus source, an acidic complexing agent and an alcohol solvent; preparing the acidic complexing agent into an acidic complexing agent aqueous solution, adding the titanium source to the acidic complexing agent aqueous solution, and stirring for 2 to 6 hours to obtain a first mixed solution; Then, adding the lithium source and the phosphorus source to the first mixed solution, stirring for 1 to 5 hours to obtain a second mixed solution; Then, adding the aluminum source to the second mixed solution and stirring for 1 to 5 hours to obtain a third mixed solution; An alcohol solvent is added to the third mixed solution to obtain a lyosol; the pH of the lyosol is adjusted to 6-8 to obtain a neutral lyosol; the neutral lyosol is dried to obtain a LATP precursor.

3. The method according to claim 2, characterized in that The lithium source is one or more of lithium carbonate, lithium nitrate, lithium hydroxide and lithium oxide; The aluminum source is one or more of aluminum carbonate, aluminum nitrate, aluminum oxide, aluminum hydroxide and aluminum chloride; The titanium source is one or more of titanic acid, tetraethyl titanate, tetrabutyl titanate and isopropyl titanate; The phosphorus source is one or more of phosphoric acid, diammonium phosphate, diammonium hydrogen phosphate and ammonium phosphate; The acidic complexing agent is one or more of citric acid, malic acid, malonic acid, succinic acid, succinic acid, glycolic acid, aminoacetic acid, lactic acid, tartaric acid and ethylenediaminetetraacetic acid; The alcohol solvent is one or more of anhydrous ethanol, ethylene glycol and glycerol; The molar ratio of lithium source, aluminum source, titanium source and phosphorus source conforms to the following chemical formula: Li 1+x Al x Ti 2-x (PO4)3, where x is 0.3 to 0.5; The mass concentration of the acidic complexing agent aqueous solution is 40-60wt.%; The molar ratio of the sum of the moles of the acidic complexing agent and the alcohol solvent to the metal cation in the liquid sol is (6-10):1; The molar ratio of the acidic complexing agent to the alcohol solvent is 1:1; The drying temperature of the neutral liquid sol is 100-150° C., and the drying time is 10-15 hours.

4. The method according to claim 1, characterized in that: In step 1), the particle size of the LATP precursor after crushing is controlled to be Dmin≥0.8μm, D10≥1.2μm, D50 is 2.0-10μm, D90≤15μm, and Dmax≤20μm; The oxidizing atmosphere is a mixed gas of air and oxygen, wherein the oxygen concentration is controlled at 21-95%; The reaction temperature 1 is 300-500°C, and the insulation time is 5-20h.

5. The method according to claim 1, characterized in that: In step 2), the inert atmosphere is a mixture of one or more gases selected from nitrogen, helium, neon, argon, krypton, xenon and radon; The reaction temperature 2 is 600-800°C, and the insulation time is 0.5-2.0h.

6. The method according to claim 1, characterized in that: In step 3), the particle size of the material after crushing is controlled to be Dmin≥30nm, D10≥50nm, D50 is 100-300nm, D90≤500nm, and Dmax≤1.0μm; The oxidizing atmosphere is a mixed gas of air and oxygen, wherein the oxygen concentration is controlled at 21-95%; Reaction temperature 3 is a step temperature, the temperature control range is 300-500°C, and the insulation time of each step temperature is 3-10h.

7. The method according to claim 1, characterized in that: In step 4), the temperature of the upper temperature zone of the dual-temperature zone reactor is controlled at 650-750° C., and the temperature of the lower temperature zone is controlled at 750-850° C.; Vacuum to maintain the air pressure in the reaction furnace chamber at -0.04 to -0.08 MPa, then blow oxygen from the bottom for 1 to 10 seconds, the oxygen pressure is 0.2 to 0.8 MPa, then let it stand for 2 to 10 minutes, then vacuum again to maintain the air pressure in the furnace chamber at -0.04 to -0.08 MPa, then blow oxygen from the top for 1 to 10 seconds, let it stand for 0.5 to 5 minutes, vibrate the furnace body once with an air hammer, and repeat 100 to 500 times.

8. A solid electrolyte nano-lithium aluminum titanium phosphate LATP material prepared by the method according to any one of claims 1 to 7, wherein the nano-LATP material is a secondary particle agglomerated from primary particles, wherein the primary particle size is ≤10nm, and the secondary particle size is ≤40nm; and the ion conductivity is ≥7×10 -4 S / cm.

9. Application of the solid electrolyte nano-lithium aluminum titanium phosphate (LATP) material according to claim 8 in lithium-ion batteries.

10. A lithium-ion battery, wherein the solid electrolyte nano-lithium aluminum titanium phosphate (LATP) material according to claim 8 is used as the solid electrolyte.

Citation Information

Patent Citations

  • Preparation method of two-dimensional ordered mesoporous carbon framework film material

    CN105565293A

  • Highly transparent quantum dot glass containing silver nanoparticles and preparation method thereof

    CN105906215A

  • Nanoscale lithium titanium aluminum phosphate material, and preparation method and application thereof

    CN115403022A

  • LATP solid electrolyte and preparation method thereof

    CN117059919A

  • Solid-state electrolytes for lithium batteries and process for production thereof

    US20170288263A1